Investigation of echocardiographic characteristics and predictors for persistent defects of patent foramen ovale or patent ductus arteriosus in Chinese newbornsAt a glance of commentary - Zhen Yuan; Long-Zhen Zhang; Bin Li; Hung-Tao Chung; Jin-Xin Jiang; John Y. Chiang; Hsin-Ju Chiang; Hon-Kan Yip; Pei-Hsun Sung (Biomedical Journal, 2021)
Background: Persistent patent foramen ovale (PFO) and patent ductus arteriosus (PDA) increase the adult risk of cryptogenic embolic stroke and chronic pulmonary hypertension. To understand the characteristics of PFO and PDA in newborns, we investigated the spontaneous closure rate and derived the determinants for residual defects. Methods: We utilized the database of congenital heart disease (CHD) in Xiamen ChangGung Memorial Hospital from 2015 to 2017 and allocated 2523 eligible newborns into four groups according to PDA, PFO, both or neither at birth. A total of 574, 1229, 202 and 518 newborns were assigned into the group of PFO and PDA, PFO alone, PDA alone and non-PFO/non-PDA, respectively. Regular echocardiographic follow-ups at baseline, 6, 12 and 24 months after birth were performed for evaluating the spontaneous closure rate in the subjects. Regression analysis was carried out to study the risk factors of residual congenital defects. Results: Newborns with PFO alone had the youngest birth age and lowest birth weight among the four groups. About one in four PDA-alone newborns had concomitant small ASD, i.e., <5 mm in diameter. Echocardiographic study showed that 71.3% and 30.8% of CHD newborns had PFO and PDA, respectively, compared to less than 10% of them having ASD or VSD. However, more than 95% of newborns with PFO or PDA closed spontaneously at 6 months, in contrast to about 30% of newborns with ASD or VSD had persistent existence of the intracardiac defects. Complex CHD significantly linked to persistent PFO or PDA at 6 and 12 months, with an adjusted hazard ratio of 9.03 (95% CI 1.97–41.46) and 12.11 (95% CI 2.11–69.72), respectively. Conclusions: Chinese newborns with PFO or PDA expressed differences in characteristics and concomitant congenital defects. Additionally, persistent PFO or PDA is strongly associated with complex CHD and requires long-term regular monitoring for future associated complications.